Networking assets [distributed generation]. - Sweet, W.
ABB's move from the business of building large power plants is a striking vote of confidence in the concept of distributed generation. The idea is that by relying on dispersed small-scale generators, combined with other distributed resources such as flywheel storage devices and sophisticated control equipment, utilities can avoid costly investments in large, often polluting central plants. They can also deploy generating assets more flexibly as needed, and at the same time reduce transmission and distribution losses. ABB makes a strong case for the usefulness of smaller-scale power in the poorer parts of the world. These areas, after all, are where some 750 million families still lack electricity. How much of a dent distributed generation can make in industrial countries and whether or not technical developments will be truly revolutionary, or more evolutionary, remains to be seen. The author discusses fuel cell power plants and microturbines (miniature gas-fired turbines). The boost for renewable energy from distributed generation is discussed as are grid interconnection issues and the limited effect on fuel conservation
Keywords: Control equipment; Dispersed small-scale generators; Distributed generation; Distribution losses reduction; Flywheel storage devices; Fuel cell power plants; Fuel conservation; Grid interconnection; Microturbines; Miniature gas-fired turbines; Renewable energy; Transmission losses reduction